Phase transfer of monosaccharides through noncovalent interactions: Selective extraction of glucose by a lipophilic cage receptor - Ryan, Theo (My University, 2002)
We have previously shown that macrotricyclic host 1a is a powerful receptor for glucopyranosyl units in the nonpolar medium of chloroform. However, the solubility properties of 1a did not permit studies of the extraction of carbohydrates from aqueous solution. This paper describes the synthesis of the new variant 1b, furnished with a highly lipophilic exterior array of 12 benzyloxy substituents. In homogeneous solution, 1b behaves much as 1a, binding n-octyl beta-d-glucoside with K(a) = 720 M(-1) in CD(3)OH/CDCl(3) (8:92). In two-phase experiments, the improved solubility of 1b allows carbohydrate extraction to be observed. Three hexoses (glucose, galactose, and mannose), two pentoses (ribose and xylose), and the two methyl glucosides are all extracted substantially into chloroform from 1 M aqueous solutions. Among the hexoses, 1b shows notable affinity and selectivity for glucose, extracting detectable amounts even from 0.1 M aqueous solutions.
PUBLISHED